Alih Kode dan Campur Kode Bahasa Makassar dan Bahasa Indonesia pada Media Sosial Facebook: Code Switching and Code Mixing of Makassarese and Indonesian on Facebook Social Media - Nurfadila, Nurfadila; Asia M, Asia M; Nojeng, Asis (Journal Studies in Indonesian Language and Literature, 2025)
This study aims to describe the form of code switching and code mixing of Makassar and Indonesian languages on Facebook social media and the factors causing it. The research method in this study is a qualitative research method. The data in this study are in the form of words, phrases, clauses or sentences containing elements of code switching and code mixing as well as the factors causing code switching and code mixing of Makassar and Indonesian languages in Facebook social media posts. The data source in this study is the upload of Facebook user accounts containing elements of code switching and code mixing of Makassarese and Indonesian languages. The data collection techniques in this study are documentation techniques and reading techniques. The results of this study indicate that the form of code switching in Facebook social media posts occurs between sentences, within sentences, and symbolic code switching. The form of code mixing is the insertion of elements in the form of words and the insertion of elements in the form of phrases. The factors causing code switching and code mixing are quoting other people, emphasizing something, the background of the speaker's attitude, and the linguistic background.